Diguanylate cyclase DgcP is involved in plant and human Pseudomonas spp. infections. (28th April 2015) - Aragon, Isabel M.; Pérez‐Mendoza, Daniel; Moscoso, Joana A.; Faure, Emmanuel; Guery, Benoit; Gallegos, María‐Trinidad; Filloux, Alain; Ramos, Cayo
Summary: The second messenger cyclic di‐GMP (c‐di‐GMP) controls the transition between different lifestyles in bacterial pathogens. Here, we report the identification of DgcP (diguanylate cyclase conserved in Pseudomonads), whose activity in the olive tree pathogen P seudomonas savastanoi pv. savastanoi is dependent on the integrity of its GGDEF domain. Furthermore, deletion of the dgc P gene revealed that DgcP negatively regulates motility and positively controls biofilm formation in both the olive tree pathogen P . savastanoi pv. savastanoi and the human opportunistic pathogen P seudomonas aeruginosa . Overexpression of the dgc P gene in P . aeruginosa  PAK led to increased exopolysaccharide production and upregulation of the type VI secretion system; in turn, it repressed the type III secretion system, which is a hallmark of chronic infections and persistence for P . aeruginosa . Deletion of the dgc P gene in P . savastanoi pv. savastanoi NCPPB 3335 and P . aeruginosa  PAK reduced their virulence in olive plants and in a mouse acute lung injury model respectively. Our results show that diguanylate cyclase DgcP is a conserved P seudomonas protein with a role in virulence, and confirm the existence of common c‐di‐GMP signalling pathways that are capable of regulating plant and human P seudomonas spp. infections.